Characterization and safety assessment of bamboo shoot shell cellulose nanofiber: Prepared by acidolysis combined with dynamic high-pressure microfluidization - Luo, Xianliang; Wang, Qi; Liu, Wangxin; Wu, Yirui; Yang, Junyi; Chen, Peng; Zhuang, Weijing; Zheng, Yafeng (Carbohydrate polymers, 2024)
The preparation of cellulose nanofiber (CNF) using traditional methods is currently facing challenges due to concerns regarding environmental pollution and safety. Herein, a novel CNF was obtained from bamboo shoot shell (BSS) by low-concentration acid and dynamic high-pressure microfluidization (DHPM) treatment. The resulting CNF was then characterized, followed by in vitro and in vivo safety assessments. Compared to insoluble dietary fiber (IDF), the diameters of HIDF (IDF after low-concentration acid hydrolysis) and CNF were significantly decreased to 167.13 nm and 70.97 nm, respectively. Meanwhile, HIDF and CNF showed a higher crystallinity index (71.32 % and 74.35 %). Structural analysis results indicated the successful removal of lignin and hemicellulose of HIDF and CNF, with CNF demonstrating improved thermostability. In vitro, a high dose of CNF (1500 μg/mL) did not show any signs of cytotoxicity on Caco-2 cells. In vivo, no death was observed in the experimental mice, and there was no significant difference between CNF (1000 mg/kg·bw) and control group in hematological index and histopathological analysis. Overall, this study presents an environmentally friendly method for preparing CNF from BSS while providing evidence regarding its safety through in vitro and in vivo assessments, laying the foundation for its potential application in food. [Display omitted]